2003
DOI: 10.2214/ajr.180.2.1800513
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoarterial Ratio and Bronchial Wall Thickness on High-Resolution CT in Asymptomatic Subjects: Correlation with Age and Smoking

Abstract: The bronchoarterial ratio is influenced by aging. The normal bronchoarterial ratio in a substantial number of subjects older than 65 years overlaps with the ratio considered to represent bronchiectasis. Thus, when this ratio is used for the quantitative analysis of pulmonary and cardiovascular disease, the influence of age should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 31 publications
8
107
3
1
Order By: Relevance
“…Hence, it was stated that when this ratio is used for the quantitative analysis of pulmonary and cardiovascular disease, the influence of age should be considered. 26 However, although the subject and control groups in the present study were not homogeneous in terms of age and gender distribution, there was no significant relation of bronchial wall thickness measurements to age and gender both in the subject and control groups. Hence, our findings seem to be free of the possible compromising influences of age and gender disparity.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Hence, it was stated that when this ratio is used for the quantitative analysis of pulmonary and cardiovascular disease, the influence of age should be considered. 26 However, although the subject and control groups in the present study were not homogeneous in terms of age and gender distribution, there was no significant relation of bronchial wall thickness measurements to age and gender both in the subject and control groups. Hence, our findings seem to be free of the possible compromising influences of age and gender disparity.…”
Section: Discussioncontrasting
confidence: 69%
“…Given the significant alterations in bronchial wall thickness associated with smoking, 26 exposure to environmental pollutants, 28 and the presence of OSA, 29 it is worth noting that our study population of subjects with mild asthma was composed of nonsmoker individuals without OSA and a history of exposure to environmental pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the key diagnostic criterion of bronchiectasis is increased bronchoarterial ratio, which is clearly influenced by age (r=0·77, p<0·0001). 54 Also the sensitivity of determining bronchiectasis radiologically is dependent upon the modality used as scans obtained on a multi-detector CT scan are more sensitive than those from a HRCT scan. 55 Thus in children, the term CSLD is used to describe a diagnosis where there are clinical symptoms of BE without HRCT confirmation.…”
Section: Chronic Suppurative Lung Disease (Csld) and Bronchiectasis (Be)mentioning
confidence: 99%
“…Matsuoka et al [27] showed a significant relationship between aging and the ratio of the diameter of the bronchus to the accompanying artery (bronchoarterial ratio). This was explained by relative hypoxemia existing in an aged cohort which caused vasoconstriction and (relative) bronchial dilation, effects which are seen among populations living at high altitude.…”
Section: Changes To the Airwaysmentioning
confidence: 99%